Genetic-Mathematical Modelling of Mutational Processes in a Population - A.N. Volobuev (Journal of Genetic Engineering, 2019)
Processes of genetic-mathematical modeling of a population development are considered. A basic distinction in the mathematical description of a family tree and a population is shown. In a family tree alternation of generations has discrete character. In a population there is a continuous alternation of generations. The method of the differential equations is applied for the description of a population. It is shown that mutational process in a population can be described with use of a Green’s function. For radiating influence on a population the universal evolutionary law is found.
Keywords: Hardy-Weinberg’s law